In vitro co-culture of Clostridium scindens with primary human colonic epithelium protects the epithelium against Staphylococcus aureus - Wang, Hao; Kim, Raehyun; Wang, Yuli; Furtado, Kathleen L.; Sims, Christopher E.; Tamayo, Rita; Allbritton, Nancy L. (Frontiers in Bioengineering and Biotechnology, 2024)
Primary human colonic epithelial cells derived from a healthy human donor were co-cultured with Clostridium scindens (C. scindens), a probiotic obligate anaerobe; Staphylococcus aureus (S. aureus), a facultative anaerobe and intestinal pathogen; or both bacterial species in tandem. The co-culture hanging basket platform used for these experiments possessed walls of controlled oxygen (O2) permeability to support the formation of an O2 gradient across the intestinal epithelium using cellular O2 consumption, resulting in an anaerobic luminal and aerobic basal compartment. Both the colonic epithelial cells and C. scindens remained viable over 48 h during co-culture. In contrast, co-culture with S. aureus elicited significant damage to colonic epithelial cells within 24 h. To explore the influence of the intestinal pathogen on the epithelium in the presence of the probiotic bacteria, colonic epithelial cells were inoculated sequentially with the two bacterial species. Under these conditions, C. scindens was capable of repressing the production of S. aureus enterotoxin. Surprisingly, although C. scindens converted cholic acid to secondary bile acids in the luminal medium, the growth of S. aureus was not significantly inhibited. Nevertheless, this combination of probiotic and pathogenic bacteria was found to benefit the survival of the colonic epithelial cells compared with co-culture of the epithelial cells with S. aureus alone. This platform thus provides an easy-to-use and low-cost tool to study the interaction between intestinal bacteria and colonic cells in vitro to better understand the interplay of intestinal microbiota with human colonic epithelium.